2022
DOI: 10.18502/ijm.v14i1.8809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extracellular vesicles of Lactobacillus rhamnosus GG on the expression of CEA gene and protein released by colorectal cancer cells

Abstract: Background and Objectives: Almost all living cells secret nano-sized structures enclosed by the lipid bilayer called extra- cellular vesicles (EVs) into their extracellular milieu. These EVs play important roles in several physiological processes as a cargo delivery system. In probiotics, EVs are the main communication tool with the host. The present study aimed to assess the effect of EVs originated from Lactobacillus rhamnosus GG on the Carcinoembryonic antigen (cea) gene expression and protein (CEA) synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…3c) and MC38 (Fig. 3d) colorectal cancer cells was reduced in a concentration-dependent manner after treatment with different concentrations of LGG-EV for 24 h. These results suggested that, as in a previous study, 32 LGG-EV have an antiproliferative effect on cancer cells in vitro .…”
Section: Resultssupporting
confidence: 85%
“…3c) and MC38 (Fig. 3d) colorectal cancer cells was reduced in a concentration-dependent manner after treatment with different concentrations of LGG-EV for 24 h. These results suggested that, as in a previous study, 32 LGG-EV have an antiproliferative effect on cancer cells in vitro .…”
Section: Resultssupporting
confidence: 85%
“…Given these results, we can assume that, unsurprisingly, not all probiotic strains may have the same health-promoting potential, although engineered EVs could represent a promising tool in cancer therapies. The remaining two articles [ 56 , 57 ] noted the same EVs’ properties on HepG2, SW480, and HT29 cells, highlighting an anti-proliferative effect on cancer cell lines ( Table 2 ). According to Behzadi et al [ 56 ], L. rhamnosus -EVs can increase the apoptotic index ( bax / bcl2 expression ratio) in liver cancer cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 60 of them, 15 and 45 concerned Gram-negative and Gram-positive bacteria, respectively. All articles assessed the size of the produced EVs, of which 49 determined it using only one technique (21 with electron microscopy [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], 19 with NTA [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ], and 9 with DLS [ 42 , 45 , 49 , 50 , 91 , 92 ,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it was recently discovered that sterile cellfree supernatant from LGG culture may promote the activity of formyl peptide receptor 1 (FPR1), which is an innate immune sensor of bacteria with anti-inflammatory and anti-angiogenic potential, expressed by both HCT-116 and HT-29 [40]. Moreover, it was proven that LGG-secreted anti-cancer biomolecule(s) may be transported within LGG-derived extracellular vesicles, with the capability to actively reduce the proliferation rate of both HT-29 and SW480 [41]. Also, nanoparticles loaded with LGG cytoplasmic lysate could significantly reduce HT-29 viability and promote apoptosis [42].…”
Section: Discussionmentioning
confidence: 99%